A year of hepatocellular carcinoma at a glance. Demographics, biochemical and radiological characteristics and treatment modalities from a specialized facility of Pakistan - Alam, Laima (Journal of the Pakistan Medical Association, 2021)
Objectives: Relation of demographics of hepatocellular-carcinoma with the aetiology. Tumour characteristics in relation to anti-viral therapy and presence of viral-DNA/RNA Treatment modalities offered Methods: This cross-sectional study enrolled all the patients aged 18-70 years with diagnosed hepatocellular carcinoma either through Triphasic Contrast-Enhanced-CT scan and/or Magnetic Resonance Imaging or biopsy presenting to the Outpatient-Department or multi-disciplinary-team meetings for the year 2019. Demographic variables, biochemical analysis including liver profile and stage of cirrhosis, viral-status, tumour staging and the treatment modalities offered were all noted. ANOVA (normal) and Kruskal-Wallis (non-normal) tests were used to compare quantitative data whereas chi-square-test and fisher-exact-test were used to compare qualitative-data. Results: Out of 195 patients with hepatocellular carcinoma, 76% were males in their fifth to sixth decades of life, 96% had cirrhosis, 94% corresponded to viral hepatocellular-carcinoma (82% Hepatitis-C-Virus, 9% Hepatitis-B-Virus and 3% coinfection), 60% of the cirrhotics landed in Child-Pugh A category with tumour staging BCLC-B being the predominant one (43.6%) and single and multiple bilateral nodules were the commonest lesions encountered. Platelets and Alanine-Transaminase had a significant relation across aetiological groups. Lymph-nodes were the most common extra-hepatic organs for metastasis and the presence of viral PCR had a significant impact on the tumour aggressiveness. Thirty-two percent of the patients were amenable to curative treatment. Conclusion: Viral infection is the main cause of rising prevalence of this tumour in Pakistan. Treatment modalities are expensive and expertise are lacking. A nationwide cancer registry is required for the exact disease burden and tumour behaviour for our population. Continuous....